Lichen planopilaris-like eruption during treatment with tyrosine kinase inhibitor nilotinib - Juliana Ribeiro Leitão; Neusa Yuriko Sakai Valente; Priscila Kakizaki; Isis Suga Veronez; Mario Cezar Pires (Sociedade Brasileira de Dermatologia, 2016)
Abstract Tyrosine kinase inhibitors are effective as a target therapy for malignant neoplasms. Imatinib was the first tyrosine kinase inhibitor used. After its introduction, several other drugs have appeared with a similar mechanism of action, but less prone to causing resistance. Even though these drugs are selective, their toxicity does not exclusively target cancer cells, and skin toxicity is the most common non-hematologic adverse effect. We report an eruption similar to lichen planopilaris that developed during therapy with nilotinib, a second generation tyrosine kinase inhibitor, in a patient with chronic myeloid leukemia resistant to imatinib. In a literature review, we found only one report of non-scarring alopecia due to the use of nilotinib.